Impact of anti-tumour necrosis factor α treatment on admissions to hospital and days of sick leave in patients with ankylosing spondylitis. Issue 12 (16th November 2004) - Listing, J; Brandt, J; Rudwaleit, M; Zink, A; Sieper, J; Braun, J
Abstract : Objective: To analyse the impact of infliximab treatment on the number of hospital inpatient days and days of sick leave in patients with active ankylosing spondylitis (AS). Methods: The data of a 2 year open extension study of a 12 week, double blind, randomised, placebo controlled trial, in which all patients with AS were treated with 5 mg/kg infliximab, were used to investigate the effect of anti-TNF treatment on admissions to hospital and days of sick leave. All patients were interviewed at baseline and at regular intervals during the study to collect this information by questionnaires. Patients who completed 2 years of treatment (n = 49) and those who did not (n = 20) were analysed separately. Sick leave analysis was restricted to currently employed patients (n = 38). Results: During the 12 months before the screening visit, 20/49 (41%) completers had been admitted to hospital. After 1 and 2 years of treatment this percentage was reduced to 5/49 (10%; p<0.01), corresponding to a significant decrease in the mean number of inpatient days: from 11.1 to 0.6 after 1 year (p<0.01) and 2.9 after 2 years (p<0.01), respectively. No changes were seen in the dropout group. Conclusion: The use of infliximab in patients with active AS reduces some important costs of AS, but additional studies with detailed cost calculations are needed.